2023
DOI: 10.1101/2023.05.11.540245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

txci-ATAC-seq, a massive-scale single-cell technique to profile chromatin accessibility

Hao Zhang,
Ryan M. Mulqueen,
Natalie Iannuzo
et al.

Abstract: Measuring chromatin accessibility is a powerful method to identify cell types and states. Performed at single-cell resolution, this assay has generated catalogs of genome-wide DNA regulatory sites, whole-organism cell atlases, and dynamic chromatin reorganization through development. However, the limited throughput of current single-cell approaches poses a challenge for implementing proper study designs, population-scale profiling, and/or very deep profiling of complex samples. To this end, we developed a 10X-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…(I) Consistent with previous studies 14,15 , the addition of 12% PEG to the reverse transcription reaction increased the number of UMIs and genes detected per cell (∼2.5- and ∼2-fold, respectively) with minor impact on the quality metrics of the ATAC modality ( Extended Data Figure 2h,i ). (II) Recently, it has been reported that barcode hopping can occur within multinucleated droplets 16,17 . In SUM-seq, barcode hopping primarily affects the ATAC modality and is mitigated by two complementary strategies: adding a blocking oligonucleotide 17 in excess to the droplet barcoding step and reducing the number of linear amplification cycles from twelve to four ( Methods ) ( Figure 1b,c and Extended Data Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(I) Consistent with previous studies 14,15 , the addition of 12% PEG to the reverse transcription reaction increased the number of UMIs and genes detected per cell (∼2.5- and ∼2-fold, respectively) with minor impact on the quality metrics of the ATAC modality ( Extended Data Figure 2h,i ). (II) Recently, it has been reported that barcode hopping can occur within multinucleated droplets 16,17 . In SUM-seq, barcode hopping primarily affects the ATAC modality and is mitigated by two complementary strategies: adding a blocking oligonucleotide 17 in excess to the droplet barcoding step and reducing the number of linear amplification cycles from twelve to four ( Methods ) ( Figure 1b,c and Extended Data Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…(II) Recently, it has been reported that barcode hopping can occur within multinucleated droplets 16,17 . In SUM-seq, barcode hopping primarily affects the ATAC modality and is mitigated by two complementary strategies: adding a blocking oligonucleotide 17 in excess to the droplet barcoding step and reducing the number of linear amplification cycles from twelve to four ( Methods ) ( Figure 1b,c and Extended Data Figure 2a ). (III) To assess the suitability of SUM-seq for asynchronous sample collection (e.g.…”
Section: Resultsmentioning
confidence: 99%